2011
DOI: 10.1111/j.1651-2227.2011.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acid status in teenage girls with eating disorders and weight loss

Abstract: The FA profile indicates low-fat intake, fat mobilization from stores and an increased conversion of essential FA at the delta-5-desaturase step during weight loss in adolescent girls with ED. Normal levels of EPA and DHA were maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
(39 reference statements)
2
31
4
Order By: Relevance
“…Although our data on elevation of LC n-3 PUFAs (EPA and DHA) seems surprising initially, Swenne et al found DPA to be higher in ED subjects [24] whereas Langan et al also reported a higher DHA level in AN subjects [21]. For n-6 PUFAs, we did not identify any significant differences in LA or ARA, but DGLA and OBA were both elevated in AN compared to controls [15].…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Although our data on elevation of LC n-3 PUFAs (EPA and DHA) seems surprising initially, Swenne et al found DPA to be higher in ED subjects [24] whereas Langan et al also reported a higher DHA level in AN subjects [21]. For n-6 PUFAs, we did not identify any significant differences in LA or ARA, but DGLA and OBA were both elevated in AN compared to controls [15].…”
Section: Discussioncontrasting
confidence: 74%
“…For n-6 PUFAs, we did not identify any significant differences in LA or ARA, but DGLA and OBA were both elevated in AN compared to controls [15]. Langan et al [21], Zak et al [23], and Swenne et al [24] found LA to be lower in AN, whereas Swenne et al [26] and Caspar-Bauguil et al [27] identified decreased ARA in erythrocyte membrane and RBC phospholipid of AN, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations